Economic Volatility, Credit Risk, and Economic Growth on Banking Stock Portfolio Performance on the Indonesia Stock Exchange (2021–2025) - Nuralima Siregar; Wardhiah Wardhiah; Rico Nur Ilham; Ristati Ristati (Jurnal Intelek Dan Cendikiawan Nusantara, 2026)
This study analyzes the effects of economic volatility (proxied by inflation), credit risk (proxied by the Non-Performing Loan ratio, NPL), and economic growth (proxied by real GDP growth) on the stock portfolio performance of Indonesia’s banking sector, measured with the Sharpe Ratio. The study is motivated by the fluctuating performance of banking stocks on the Indonesia Stock Exchange (IDX) amid shifting global and domestic macroeconomic conditions, and is grounded in Modern Portfolio Theory and risk–return theory. A quantitative approach was applied to panel data from banks listed on the IDX selected through purposive sampling, which were analyzed using panel data regression with the Fixed Effect Model (FEM) as indicated by the Chow test. The results show that inflation has a positive effect on banking stock portfolio performance, although the effect is only weakly significant, so the hypothesis proposing a negative and significant effect is rejected. The Non-Performing Loan ratio has a negative and significant effect, so the corresponding hypothesis is accepted. Real GDP growth has a positive and significant effect, consistent with the hypothesized direction, so the corresponding hypothesis is accepted. These findings indicate that economic growth is the most dominant and consistent driver of banking stock portfolio performance, followed by credit risk with a smaller contribution, while inflation had no conventionally significant effect during the study period.